1984
DOI: 10.1097/00012272-198401000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal competence and communication in the delivery of nursing care

Abstract: Despite the importance generally attributed to communication in nursing, little systematic attention has been directed toward exploring the interface between communication and the delivery of nursing care. The primary factors that have tended to impede research have been the inability of emerging models of nursing to conceptualize communication from an adequate perspective and level and the lack of theoretic exemplars for guiding specific lines of investigation. This article suggests that one potential exempla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Although the financial constraints of using professional nursing staff in long-term care settings are understood, professional staff could be used to guide care of elders presenting difficult care problems. The relationship between professional status and interactive behavior has been supported by at least one other study (Kasch, 1984); thus, the use of professional nursing staff needs to be considered in care. Given the relationship of knowledge of dementia to several caregiver behaviors, inservice education programs designed for all levels of nursing practice and focused on increasing the caregivers' understanding of the disease and its effects on the elder may facilitate positive caregiving behaviors.…”
Section: )mentioning
confidence: 95%
See 1 more Smart Citation
“…Although the financial constraints of using professional nursing staff in long-term care settings are understood, professional staff could be used to guide care of elders presenting difficult care problems. The relationship between professional status and interactive behavior has been supported by at least one other study (Kasch, 1984); thus, the use of professional nursing staff needs to be considered in care. Given the relationship of knowledge of dementia to several caregiver behaviors, inservice education programs designed for all levels of nursing practice and focused on increasing the caregivers' understanding of the disease and its effects on the elder may facilitate positive caregiving behaviors.…”
Section: )mentioning
confidence: 95%
“…They found that age was negatively correlated with empathic communication and that years in nursing service revealed a curvilinear relationship with empathy, with 1 to 5 years corresponding to the highest level of empathic communication. In a sample of outpatient dialysis nurses, Kasch (1984) found the ability to produce patient-centered messages was more positively related to the nurse's educational level and occupational status than to length of service.…”
mentioning
confidence: 97%
“…The dynamics of nurse–patient interactions at the bedside depend largely on the nurse's interpersonal competences and communicative skills (Kasch 1984, 1986 & Shattell 2004). When patients are severely ill their ability to assess and negotiate the agenda of nursing care is limited (Cahill 1998, Shattell 2004, Schoot et al.…”
Section: Introductionmentioning
confidence: 99%
“…Communication consists in understanding both verbal and nonverbal messages; it is an ability to share experiences with others, which means that the timing of the message is also important for interaction. For the caring relationship to be successful, it is important not only that there is an awareness and shared understanding of the goals of nursing and that the relationship is based on interaction, but also that the professional nurse work continually to develop her skills of interaction (Bernstein & Bernstein, 1980;Bradley & Edinberg, 1982;Kasch, 1984;Leino-Kilpi, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%